Scoreboard Tool - Srinivasan, Anush (Kansas State University, 2009)
Scoreboard tool is a web application developed to provide a platform where administrators can conduct quizzes (typically in an organization) or employees can take a quiz (individually or in a team). These quizzes are generally conducted to improve the knowledge of the users (typically employees) taking the quiz. This project is a tool where the user can take online quizzes which comprise of various categories like technology, science, math etc . The categories have various sub-categories. The admin can also perform CRUD on teams. The quizzes are created by the admin using a database which has the questions for the quizzes. The quizzes are basically divided into quizzes with multiple choice questions and timed quizzes where a user has a specified time to complete the quiz. Once a user logs in he can view his quiz history where he can view the scores of the various quizzes taken and also the time and date when taken. At the end of the quiz the user is given the option of rating the quiz and also entering his/her opinion of the quiz. The users will also have an option to view their scores graphically and compare their scores with other teams in the form of reports and also as graphs. The important feature of this application is that the scores will be reported using reporting services. And another important feature is instead of manually testing the application test cases will be written for automated testing.
Keywords: Scoreboard Tool in C#.net; Computer Science (0984)